Contextualizing the Meaning of Al-Ẓān in Q.S. Al-Hujurat 12 (Charles Sanders Pierce Semiotic Analysis) - Sofyan, Muhammad Ilham (Aqwal: Journal of Qur'an and Hadis Studies, 2023)
This research aims to portray various Qur'anic interpretations of the word al-Ẓān based on the projection of signs through Charles Sanders Pierce's semiotic approach. The author limits the object of research to Q.S. Al-Hujurat 12, based on the interpretation of classical to contemporary mufassirs. This research is included in the type of literature (library research), using descriptive-analytical method to identify the interpretation of al-Ẓān in the books of interpretation and then apply it with the concept of trichotomy (representament, object, interpretant). Pierce's semiotics sees a sign as always evolving and continuous in nature, as far as new interpretations are found, in this context other semantic meanings of the word az-Ẓān. The findings in this study confirm that prejudice (az-Ẓān) in Q.S. Al-Hujurat 12 has various meanings, namely: the spread of bad news, good prejudice, the boundary between belief and doubt, and bad prejudice. These meanings descend into moral values that are relevant to the current context. In the current context, spreading bad news is similar to hoaxes and hate speech. Another portrait is seen in the phenomenon of overthinking, which is rooted in excessive prejudice, which certainly has negative implications for physical and psychological health.